2007
DOI: 10.1111/j.1440-1746.2006.04542.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of common transforming growth factor beta‐1 gene polymorphisms in gastric and duodenal ulcer disease: Pilot study

Abstract: These findings indicate that the Leu10Pro and C-509T polymorphisms may be involved in the modulation of expression of the TGF-beta1 gene, and therefore a predisposition to peptic ulcer disease could be linked to particular alleles of this gene. In particular, a possible role of TGF-beta1 in the pathogenesis of gastric ulcer disease is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…These growth factors trigger mitogenic and survival pathways utilizing Ras, MAPK, PI-3K/Akt, PLC-␥, and Rho/Rac/actin signaling. TGF-␤ is well known as a multifunctional cytokine that regulates many biological processes, including cell proliferation, differentiation, adhesion, intercellular signaling, and the accumulation of extracellular matrix proteins and thus has an essential role during wound healing and tissue repair (23,24). Many studies over recent years have suggested that TGF-␤ plays a crucial role in both inflammation and tissue injury repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These growth factors trigger mitogenic and survival pathways utilizing Ras, MAPK, PI-3K/Akt, PLC-␥, and Rho/Rac/actin signaling. TGF-␤ is well known as a multifunctional cytokine that regulates many biological processes, including cell proliferation, differentiation, adhesion, intercellular signaling, and the accumulation of extracellular matrix proteins and thus has an essential role during wound healing and tissue repair (23,24). Many studies over recent years have suggested that TGF-␤ plays a crucial role in both inflammation and tissue injury repair.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies over recent years have suggested that TGF-␤ plays a crucial role in both inflammation and tissue injury repair. Polonikov et al (23) showed that TGF-␤ may play an essential role in peptic ulcer disease, and proposed that the biological effects of TGF-␤ 1 , an isoform of TGF-␤, are divided into four groups. Firstly, TGF-␤ 1 is likely to be needed to restrict local damage to the gastric mucosa after acute injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control group included blood donors, healthy volunteers and hospital-based patients (all subjects were recruited from the surgical, traumatic, and infectious divisions of Kursk hos pitals) with normal blood pressure and without cardiovas cular or other chronic diseases. The control group was recruited over the same periods of time [34][35][36][37][38]. To ensure an ethnically homogeneous population, only Russian resi dents living in Central Russia for at least two generations have been included in the study.…”
Section: Study Participantsmentioning
confidence: 99%
“…The control group included blood donors, healthy volunteers as well as hospital-based patients recruited from surgical, traumatic, infectious divisions of Kursk hospitals without cardiovascular and other chronic diseases. The control group was recruited over several periods in the framework of our previous studies (Polonikov et al, 2007;Polonikov et al, 2008;Polonikov et al, 2009;Bushueva et al, 2014;Polonikov et al, 2015;Polonikov et al, 2017). Demographic and clinical characteristics of the study subjects are listed in Table 1.…”
Section: Study Participantsmentioning
confidence: 99%